About the First Record of the Genus Chonecolea (Chonecoleaceae, Marchantiophyta) in Paraguay and Its Differences to Related Species - Flores, Jorge Rafael (2015)
Chonecolea doellingeri (Nees) Grolle, whose South American record is restricted to Argentina and Brazil, is reported for the first time for Paraguay. Additionally, its differences to related species are discussed and SEM microphotographs are provided.